2006
DOI: 10.1038/sj.jcbfm.9600331
|View full text |Cite
|
Sign up to set email alerts
|

Role of P450 Aromatase in Sex-Specific Astrocytic Cell Death

Abstract: Female animals are protected from ischemic brain damage relative to age-matched males, in part through protection provided by endogenous estradiol. In brain, estradiol is produced from testosterone by cytochrome P450 aromatase (cyp 19), a steroid synthetic enzyme present in astrocytes. We tested the hypothesis that astrocytes derived from neonatal female rat brain are less susceptible than male cells to oxygen-glucose deprivation (OGD), and that this endogenous protection is associated with enhanced aromatase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
116
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 44 publications
5
116
1
2
Order By: Relevance
“…Three types of pups were born: wild-type (WT), knockout (ArKO), and heterozygote (HT). In agreement with data generated in sex-specific rat astrocytes (Liu, et al, 2007), we found that female WT mouse astrocytes are more resistant to oxygen-glucose deprivation (OGD) than male WT mouse astrocytes. It is important to note that male sensitivity and female resistance to OGD are observed across species.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Three types of pups were born: wild-type (WT), knockout (ArKO), and heterozygote (HT). In agreement with data generated in sex-specific rat astrocytes (Liu, et al, 2007), we found that female WT mouse astrocytes are more resistant to oxygen-glucose deprivation (OGD) than male WT mouse astrocytes. It is important to note that male sensitivity and female resistance to OGD are observed across species.…”
Section: Discussionsupporting
confidence: 79%
“…We reported that astrocytes isolated from neonatal cortex exhibited marked sex differences in sensitivity to oxygen glucose deprivation (OGD) in part due to higher aromatase expression in female astrocytes compared to male cells. The aromatase inhibitor Arimidex abolished sex differences in OGD-induced cell death (Liu, et al, 2007), suggesting that sex differences in ischemic cell death are related to aromatase expression (Liu, et al, 2007). Such experiments conducted in steroid-free media indicate that some mechanisms of injury (or survival) may be linked to the genetic sex of the cell.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Indeed, endogenous protective processes have been reported in cultured astrocytes from female neonatal mice that are more resistant to injury and cell death than male astrocytes. 33 The finding that MAP-2 expression in the subgranular zone was not affected by gestational age suggests that neuronal proliferation is advanced at the age of preterm delivery used in this study. The possibility that there are long-term neurodevelopmental effects of a deficit in progesterone or allopregnanolone exposure in preterm neonates requires further investigation.…”
Section: Discussionmentioning
confidence: 68%
“…Extragonadal estrogen synthesis by local tissue aromatase becomes the major source of estrogen in postmenopausal women (47,51). Within the brain, aromatase has been localized to multiple cell types, including neurons, astrocytes, smooth muscle cells, and endothelial cells (6,12,16,25,31,48).…”
mentioning
confidence: 99%